Mapping of Peatland Subsidence in Peat Hydrology Unit Jangkang River – Liong River in Bengkalis Island: Pemetaan Subsiden di Kesatuan Hidrologi Gambut Sungai Jangkang – Sungai Liong Pulau Bengkalis - Edi, Harisman; Barus, Baba; Baskoro, Dwi Putro Tejo (Jurnal Ilmu Tanah dan Lingkungan, 2019)
Subsidence is an important issue in the utilization of peatland. If the subsidence is not controlled, it will cause flooding and land degradation. This research develops subsidence mapping taken into account factors influencing the subsidence using regression analysis stepwise method. The result shows the influenced by age of plants, landuse, bulk density 50-100 cm, water table, water level in drainage canal and distance from the drainage canal with equation function Y = -28.240 + 1.241 X1 + 0.023 X2 + 4.866 X3 + 0.370 X4 – 97.089 X5 – 0.209 X6 + 0.298 X7. The range of 0-50 cm subsidence covers 13,472 ha occupied largely by rubber plantation of 4,013 ha, 50-100 cm subsidence covers 2,147 ha occupied largely by rubber plantation of 813 ha, and more than 100 cm subsidence covers 261 ha occupied largely by palm plantation of 88 ha.Keywords: Bengkalis, landuse, mapping, peatland, subsidence